OPTIMASI KAPASITAS MASYARAKAT DALAM MENCEGAH KRISIS KESEHATAN REPRODUKSI REMAJA (Jurnal Mitra Masyarakat (JMM), 2023)
Adolescents often experience physical and reproductive changes before they're emotionally and mentally mature, which can lead to issues like drug and alcohol abuse, unsafe sex, HIV/AIDS, and malnutrition. Health workers can help by educating both teenagers and their communities on reproductive health. Community service activities in the form of education are carried out to optimize the role of teenagers in preventing health problems. The activity participants consisted of teenagers, school guidance and counseling teachers, and parents totaling 401 people. This activity aims to increase the understanding and role of teenagers, teachers, and parents regarding teenagers' health and quality of life. The pre-test and post-test scores show an increase in the average score which means there is an increase in participants' understanding of adolescent problems and potential (sig.= 0.000). Online education can be used to increase the role of teenagers, teachers, and parents to strengthen support for youth groups.